2021
DOI: 10.1186/s12906-021-03445-5
|View full text |Cite
|
Sign up to set email alerts
|

Activity of antifungal drugs and Brazilian red and green propolis extracted with different methodologies against oral isolates of Candida spp.

Abstract: Background Oral candidiasis is an opportunistic disease caused by fungi of the Candida genus. The occurrence of Candida spp. resistance to the commercial antifungal drugs points to the search for alternative treatments. Propolis has been successfully used in the treatment of infectious diseases for centuries. It has been proposed that an ultrasound pretreatment in the propolis extraction protocol can enhance the concentrations of molecules with antimicrobial activities in the final extract. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Therefore, it can be concluded that the synergy of action of all components of propolis extract determines the antifungal activity. However, it should be noted that the extracts of Brazilian propolis showed very wide variability in antifungal activity, e.g., according to Freires et al [54] Brazilian reed propolis showed MIC = 2.0 µg/mL), Siqueira et al [75] revealed for the same type of propolis showed MIC = 32-64 µg/mL, whereas Sokolonski et al [13] stated values of MIC from 0.5 to more than 8 mg/mL (Table 2). This indicates the need to standardize the chemical composition of the different types of propolis collected all over the world.…”
Section: Collected Data Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it can be concluded that the synergy of action of all components of propolis extract determines the antifungal activity. However, it should be noted that the extracts of Brazilian propolis showed very wide variability in antifungal activity, e.g., according to Freires et al [54] Brazilian reed propolis showed MIC = 2.0 µg/mL), Siqueira et al [75] revealed for the same type of propolis showed MIC = 32-64 µg/mL, whereas Sokolonski et al [13] stated values of MIC from 0.5 to more than 8 mg/mL (Table 2). This indicates the need to standardize the chemical composition of the different types of propolis collected all over the world.…”
Section: Collected Data Analysismentioning
confidence: 99%
“…Generally, ethanolic extracts of propolis, which come from different regions of Brazil, are investigated most often (199 publications in PubMed between 2011 and 2021) [8,14,17,40,54]. High-quality chemical analysis mainly concerns two types of propolis such as Brazilian red propolis (using gas chromatography coupled to mass spectrometry [54], and liquid chromatography-high-resolution mass spectrometry [53]), and Brazilian green propolis (using liquid chromatography-high-resolution mass spectrometry [53], and highperformance liquid chromatography (HPLC-DAD) [13]. Table 1.…”
Section: Plant Animal and Environmental Factors Influencing The Chemi...mentioning
confidence: 99%
See 3 more Smart Citations